The Home as Factory Floor: Employment and Remuneration of Home-Based Workers - Cunningham, Wendy; Gomez, Carlos Ramos (World Bank, Washington, D.C., 2013)
Home-based work, defined as nonprofessionals who perform market work from their homes, is an increasingly recognized form of employment in Latin America. The majority of the research on this segment of the labor force relies on small sample, qualitative data, which find that home-based workers are women, children, and adults with disabilities with low skills who work long hours for low wages. The authors use a large random sample of control groups of non-home-based workers, including men, in their analysis and examine the home-based work sector in Brazil, Ecuador, and Mexico in 1999. Their results show that in all three countries, women are overrepresented among home-based workers, particularly older women, those with low levels of education, and those with children or spouses, unlike men for whom these factors do not matter. Female home-based workers earn 25-60 percent less an hour than do non-home-based working women and they work one-third to one-half as many hours each week. Home-based working men, on the other hand, earn 0-17 percent less than do men who do not work from their homes, and they only work 10 percent fewer hours a week. The wage and work hour gaps for women are largely related to marital status, not the presence of children, suggesting that simply being the primary caregiver in the household, regardless of the actual time constraints (children) is the key factor to differences between home-based working women and those who work outside of their homes.